História natural da jararaca endêmica da Caatinga Bothrops erythromelas Amaral, 1923 (Serpentes: Viperidae: Crotalinae): dieta, morfologia, dimorfismo sexual e período reprodutivo - Silva, Willianilson Pessoa da (2021)
Natural history studies describe the way of life of organisms and where they are inserted as well as their role in the ecosystem, being of great importance and the conservation of species. Brazil is a country comprising 795 species. Of this total, there are 414 by species of snakes. Among Brazilian snakes, only 68 species are responsible for venomous accidents in Brazil. Most genera are produced by species belonging to the group. This genus has representatives in all biomes of the country, including the Caatinga, which is currently the third most degraded domain in Brazil. This has been neglected for a long time, mainly due to the belief that it is valid for a domain without identity. Currently, we know that the Caatinga is quite rich and diverse, including endemic species such as the jaraca-da-seca Bothrops erythromelas It is one of the smallest species of the genus, with variations in size and color, but its evolutionary history, ecology and other aspects are still are little known. In this work we verified natural aspects of this species, scientific samples of the history deposited in collections in northeastern Brazil. The present work brings information about reproduction, feeding and the presence of sexual dimorphism. We verified that this species presents sexual dimorphism in total length, Rostrum Cloacal length, tail size and number of subcaudal scales. We are breeding seasonally, mainly in the dry period Bothrops erythromelas a generalist diet and does not present ontogenetic seeds, feeding on endothermic and ectothermic prey.